2016
DOI: 10.1016/j.contraception.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Polidocanol induced tubal occlusion in nonhuman primates: immunohistochemical detection of collagen I-V

Abstract: ObjectiveIntrauterine administration of polidocanol foam (PF) can create fallopian tube occlusion in nonhuman primates. The objective of this study was to determine if PF-induced tubal obstructions contain collagen in the extracellular matrix.Study designWe compared tissue samples of the intramural fallopian tube obtained from previous studies evaluating the effects of intrauterine infusion of 5% PF 2–12 weeks after treatment. Serial sections of the intramural portion of the fallopian tube obtained from repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Our long-term goal is to develop a low-cost, non-surgical approach to female permanent contraception. We have shown that a single treatment with 5% polidocanol foam results in a permanent collagen occlusion of the intramural Fallopian tube in non-human primates ( 7 , 8 ) and female baboons successfully treated do not become pregnant ( 9 ). However, not all females treated with polidocanol foam develop bilateral occlusion after a single treatment as is the case with quinacrine sterilization ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our long-term goal is to develop a low-cost, non-surgical approach to female permanent contraception. We have shown that a single treatment with 5% polidocanol foam results in a permanent collagen occlusion of the intramural Fallopian tube in non-human primates ( 7 , 8 ) and female baboons successfully treated do not become pregnant ( 9 ). However, not all females treated with polidocanol foam develop bilateral occlusion after a single treatment as is the case with quinacrine sterilization ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Polidocanol (hydroxyl-polyethocydodecane) is a synthetic long-chain fatty acid alcohol approved by the U.S. FDA for the treatment of varicose veins [56]. This agent, when administered transcervically in baboons, caused scarring that obliterated the lumen of the oviduct, resulting in pregnancy prevention [57,58,59]. This approach has not entered human clinical trials.…”
Section: New Methods In Developmentmentioning
confidence: 99%